The bioaccumulation testing strategy for manufactured nanomaterials: physico-chemical triggers and read across from earthworms in a meta-analysis. Issue 11 (4th October 2021) - Handy, R. D.; Clark, N. J.; Vassallo, J.; Green, C.; Nasser, F.; Tatsi, K.; Hutchinson, T. H.; Boyle, D.; Baccaro, M.; van den Brink, N.; Svendsen, C.
Abstract : How to use chemical triggers and invertebrate tests in the lower tiers of a bioaccumulation testing strategy. Abstract : Little is known about the bioaccumulation potential of manufactured nanomaterials (MNs). For traditional chemicals, the Organisation for Economic Co-operation and Development (OECD) Test Guideline (TG) 305, bioaccumulation in fish is often used. However, for MNs, there are no approved processes to trigger or waive this test, or consider alternatives to vertebrate animals. The aim of the present study was to conduct a meta-analysis of existing data sets on particle properties and bioaccumulation in earthworms to understand what particle metrics could be used as a trigger for bioaccumulation testing. An apparent steady state tissue concentration of metal from MNs exposure in the earthworm ( Eisenia fetida ) was evident following exposures to Ag nanoparticles (NPs), CuO NPs and CdTe quantum dots (QDs). This allowed the derivation of nano bioaccumulation factors (nBAFs), calculated using soil and earthworm tissue metal concentrations. A prediction equation using all the particle metrics correlated with BAFs was possible. Similarly, nano biomagnification factors (nBMFs) were calculated in the rainbow trout ( Oncorhynchus mykiss ) tissue, relative to the concentration of total metals in the fish diet. Pearson's correlations were found to be significant, with p < 0.05 for nBMFs for the liver, mid intestine, hind intestine and kidney relative to the earthworm tissue nBAFs. Together these data indicate that bioaccumulation measurements in earthworms for metallic MNs could be predictive of those values in fish, and that there is scope to predict the bioaccumulation potential of MNs with confidence from a few simple particle metrics.